The Impact of COVID-19 on Hungarian Freight Transport - Huszárik Erika Seres; Mura Ladislav; Farkas Iván Zsolt (Logi)
The logistics and transport sector has experienced unprecedented growth over the past decade. It is one of the most dynamically developing business sectors. The unexpected pandemic crisis had a severe impact on the business activities of various entities, significantly affecting not only the existence of business entities but also their business success. The goal of the present research was to examine the emergence and impact of COVID-19, with a particular focus on the logistics sector, primarily transport activities. The study is addressing freight transport in Hungary, using a questionnaire survey that included the participation of 312 business entities. Data processing was conducted uisng SPSS statistical software as a quantitative method. Based on the research results, the authors recommend the implementation of innovations and green logistics practices to ensure sustainable business activities within this sector. Based on the findings, it can be stated that the more diverse a company’s activities are, and the faster it can respond to economic challenges, the smaller the losses it will incur.